Factor Analysis of Intention to Use Open-Source ERP: A Case Study from East Java Area - Kusumawati, Aris; Asfari, Ully; Ramadhanti, Aisyah Putri Amni; Jaya, Ekky Dea Audry; Hadyanto, Farid Duta (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2023)
Open-source ERP is an information system that supports the digitization of an organization's business so that it can support business continuity in an uncertain environment during the new normal while still implementing health protocol. In fact, only a few small to medium-sized organizations have adopted it. This research aims to examine the significant factors that influence the intention to use or adopt an open-source ERP system in the MSME-based new normal era. In the manner of exploring technological readiness's positive and negative effects on cognitive factors (H1 and H2), environmental uncertainty, and cognitive and organizational readiness on intention to use (H3, H4, H5). There are 420 respondents collected by non-probability sampling and have been analyzed using PLS-SEM based on five subsectors of the small and medium-scale organizations (i.e.: agricultural, fishery, fashion, handicrafts, and culinary). This research confirms that the conceptual model and the five hypotheses proposed previously have been fully proven. The findings of this study prove that the intention to adopt an open-source ERP system is influenced by readiness factors (positive and negative technological, cognitive, and organizational) and environmental uncertainty due to the past COVID-19 pandemic.